Brief maternal exposure of rats to the xenobiotics dibutyl phthalate or diethylstilbestrol alters adult-type Leydig cell development in male offspring - Ivell, Richard; Heng, Kee; Nicholson, Helen; Anand-Ivell, Ravinder (Nature Publishing Group, 2013)
Maternal exposure to estrogenic xenobiotics or phthalates has been implicated in the distortion of early male reproductive development, referred to in humans as the testicular dysgenesis syndrome. It is not known, however, whether such early gestational and/or lactational exposure can influence the later adult-type Leydig cell phenotype. In this study, Sprague-Dawley rats were exposed to dibutyl phthalate (DBP; from gestational day (GD) 14.5 to postnatal day (PND) 6) or diethylstilbestrol (DES; from GD14.5 to GD16.5) during a short gestational/lactational window, and male offspring subsequently analysed for various postnatal testicular parameters. All offspring remained in good health throughout the study. Maternal xenobiotic treatment appeared to modify specific Leydig cell gene expression in male offspring, particularly during the dynamic phase of mid-puberty, with serum INSL3 concentrations showing that these compounds led to a faster attainment of peak values, and a modest acceleration of the pubertal trajectory. Part of this effect appeared to be due to a treatment-specific impact on Leydig cell proliferation during puberty for both xenobiotics. Taken together, these results support the notion that maternal exposure to certain xenobiotics can also influence the development of the adult-type Leydig cell population, possibly through an effect on the Leydig stem cell population.